Impact of TiO2 nanoparticles and nanowires on corrosion protection performance of chemically bonded phosphate ceramic coatings. Issue 4 (15th February 2022) - Liu, Yaxuan; Wang, Yongguang; Bian, Da; Wu, Wangping; Guo, Pushan; Zhao, Yongwu
Abstract: The impact of the addition of TiO2 nanoparticles and nanowires on the morphology, phase characteristics, contact angle, and electrochemical performance of chemically bonded phosphate ceramic coatings (CBPCs) was investigated. The chemical composition and surface morphology of the TiO2 nanoparticle and nanowire modified with and without (heptadecafluoro-1, 1, 2, 2-tetradecyl) trimethoxysilane were characterized. Results indicated that the hydrophobic –CF2 – and –CF3 groups were successfully introduced into the TiO2 nanoparticles and nanowires after modification. Corrosion resistance of CBPCs with TiO2 was evidently improved compared with that without TiO2 . Such improvement was mainly due to the combined effects of low surface energy materials and micro/nano structures. In addition, CBPCs with TiO2 nanowires exhibited higher hydrophobicity and corrosion resistance than those with TiO2 nanoparticles because of the special columnar structure of the nanowires.